Uso de natamicina no controle do desenvolvimento de fungos em salame tipo italiano - Brustolin, Jean Carlos (2009)
This study had as objective to evaluate the behavior of natamycin in different concentrations and forms of application to control the growth of molds in Italian type salami matured in maturation rooms wood through counting of molds and yeasts with swabs and photographic monitoring weekly. Was also evaluated the effect of natamycin on the physical chemical aspects such as water activity, moisture, fat and protein and the sensory aspect evaluated by multiple comparison test. Salami that were evaluated had their casings hydrated with a solution of natamycin with 0.1%, 0.05% and 0,025% before the stuffed and the 0.1% sprayed after smoking in smoking room. It was found that there was a lower count of molds and yeasts in the samples treated with 0.1% natamycin both by immersion or by spraying. The natamycin did not interfere in the sensory and physical chemical aspects.